Analysis of Al Haydawan (Boerhavia elegana) Seed Extracts: Mineral Composition, Total Phenolic Content, and Primary Antioxidant Activity - Almegairshah, Suad Ali Sulaiman; Ali, Asmahan Azhari; Mohamed, Sahar Hassan Salah (Journal of agricultural, environmental and veterinary sciences, 2024)
Many consumers are increasingly seeking safer alternatives to synthetic additives in food, leading to a preference for healthier options. Consequently, the food industry is exploring various plant-based preservatives. These natural ingredients offer antioxidant benefits, boost bioactive compound levels, and enhance food products' microbiological stability. It is also crucial to assess how these preservatives influence the sensory attributes of new items, as they may produce flavors or textures that some consumers find unappealing. Boerhavia elegana L. (from the Nyctaginaceae family) is a medicinal plant known for treating kidney issues, urinary problems, and blood purifying. This study investigated the differences between aqueous and ethanolic AlHaydawan extracts regarding mineral, antioxidant, and phenolic content on cold storage's first and seventh days.
Keywords: Al Haydawan (Boerhavia elegana); Minerals; Total phenolic content; antioxidants; solvent extraction